An intelligent interface agent for an airline company web portal - Luis Sá Barbosa (2009)
In this paper we introduce an implementation of an Intelligent Interface Agent to support the use of a web portal in an airline company. The interface agent architecture and data model is presented. We formalized concepts such as relevance and proximity regarding the data structure. The concepts of personal opinion and general opinion are also introduced and formalized. A statistical analysis was performed to obtain the best value when processing the general opinion. Some results of that analysis are presented and we conclude discussing our work and presenting future improvements.